Correlation of serum iron and ferritin levels in patients of cholelithiasis and comparison with healthy individuals - Dadhich, Yogendra; Bhardwaj, Girish; Goel, Gaurab; Mandia, Rajendra (International Surgery Journal, 2019)
Background: Gall stones have afflicted man kinds since antiquity. Gall stone disease is prevalent, major source of morbidity and costly health problem. Presence of stones in the gallbladder is referred to as cholelithiasis, from the Greek chol-(bile)+lith (stone)+iasis-(process). If gallstones migrate into the ducts of the biliary tract, the condition is referred to as choledocholithiasis. Methods: It is case control study. Inclusion criteria were, patients aged above 18 years suffering from cholelithiasis confirmed by USG. The exclusion criteria were, patients having hematological disorder, having any systemic disease leading to iron deficiency, on drugs causing gallstones and pregnant females. Results: Study shows females were affected more in case (64%) and control (76%) group with mean age was of case (42.84 years) and control (40.64 years) group. 24% of patients was anaemic in cases. The mean serum cholesterol between cases and control was statistical insignificant (p=0.252). The mean serum ferritin between cases and control was statistical insignificant (p=0.800). Conclusions: The study of 100 cases, based on serum iron, serum cholesterol, serum ferritin and hemoglobin, concludes that the disease is more prevalent in female gender. Serum ferritin association is insignificant as it increases other condition with inflammation also. Low serum iron level associated with high risk of cholelithiasis as this may lead to super saturation of bile.